Copper(II) Acetylacetonate: An Efficient Catalyst for Huisgen‐Click Reaction for Synthesis of 1, 2, 3‐Triazoles in Water. Issue 8 (2nd June 2017) - Jiang, Yuqin; Li, Xingfeng; Li, Xiyong; Sun, Yamin; Zhao, Yaru; Jia, Shuhong; Guo, Niu; Xu, Guiqing; Zhang, Weiwei
Abstract : An efficient and green copper(II) acetylacetonate‐catalyzed protocol for the Huisgen‐click reaction in water at 100 °C has been established. The protocol was not only suitable for the reaction between organic azides and alkynes, but also suitable for one‐pot three‐component reaction among alkyl halides, NaN3 and alkynes. Abstract : An efficient and green copper(II) acetylacetonate‐catalyzed protocol for the Huisgen‐ click reaction in water at 100 °C has been established. The protocol was not only suitable for the reaction between organic azides and alkynes, but also suitable for one‐pot three‐component reaction among alkyl halides, NaN3 and alkynes